METHODS OF CREATING AN INFORMATIONAL EDUCATIONAL ENVIRONMENT IN IMPROVING THE QUALITY OF EDUCATION - Davletov, Nurlibay Aymuratovich (Innovative Development in Educational Activities, 2024)
The content of the article mentions that the use of information and communication technologies in the educational process is the need of the hour, and the main tasks of information and communication technologies in the implementation of information and methodical support in the educational process